A simple, reliable and cost-effective, high temperature dilatometer for bulk thermal expansion studies on solids. (October 2016) - Manoj, N.; Jain, Dheeraj; Gautam, J.K.; Thomas, K.C.; Sudarsan, V.; Pillai, C.G.S.; Vatsa, R.K.; Tyagi, A.K.
Graphical abstract: Highlights: A simplified high temperature dilatometer has been designed, fabricated and tested. Simple design and ease of operation/maintenance are unique features of the system. Baseline correction methodology to evaluate thermal expansion has been provided. Overall accuracy of system is ±3% using NIST sapphire reference from RT to 1373 K. Equipment is useful in small-scale industries, research labs and academic institutes. Abstract: A simplified, highly reliable, cost effective high temperature (RT-1373 K) vertical dilatometer system, based on linear variable differential transformer (LVDT) has been designed, fabricated and tested for measurement of linear thermal dilation of solid samples. Unique features of this fully automated PC-controlled system are: simple design, fabrication from locally available components, ease of operation and maintenance, good temperature resolution (1 K), wide measurement range (±1 mm, with 100 nm resolution), microcontroller-based data acquisition hardware and a simple windows-based software. The system has been tested for its performance using NIST sapphire reference and high purity metals including aluminum and nickel. Overall accuracy of the system for measurement of linear thermal dilation is within 3% of the reported values for NIST sapphire. The system is a good example of a simple experimental facility for routine thermal expansion characterization of solids. Combination of simplified design, automation and reliable performance without using sophisticated instrumentation/control systems makes it a novel cost effective thermo-analytical equipment, which can be put to widespread routine usage for researchers, academy and small/medium-scale industries.